2002
DOI: 10.1007/s00223-001-2037-3
|View full text |Cite
|
Sign up to set email alerts
|

Activin A Increases the Bone Mass of Grafted Bone in C3H/HeJ Mice

Abstract: Activin A, a member of the TGF-b superfamily, is abundant in bone matrix, but little is known about its physiological role in bone metabolism. The present study was undertaken to determine whether topical activin A can increase the bone mass of isografted bone. The tibiae were bilaterally dissected from a donor C3H/HeJ mouse and transplanted subcutaneously in the dorsal region of a recipient mouse. One isografted tibia was topically infused for either 1, 2, 3, or 4 weeks with activin A, using an osmotic minipu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…This hypothesis is further corroborated by several experimental and clinical observations which show that Act A signalling pathway is deregulated in some primary bone tumors, such as osteosarcoma (Gobbi et al, 2002;Matsuyama et al, 2003), chondrosarcomas (Masi et al, 2002) and osteochondromas (Deirmengian et al, 2008) and in tumors which preferentially Promotes bone formation and fracture healing and increases bone mass of grafted bone in mice Hirotani et al (2002), Sakai et al (2000b), Sakai and Eto (2001) Abnormal craniofacial development in knock out mice deficient in either activin A or type II receptor Matzuk et al (1995a), Matzuk et al (1995b) a The effects of activin on osteoblasts are controversial (see text for details).…”
Section: Activin In Metastatic Bone Diseasesupporting
confidence: 53%
See 1 more Smart Citation
“…This hypothesis is further corroborated by several experimental and clinical observations which show that Act A signalling pathway is deregulated in some primary bone tumors, such as osteosarcoma (Gobbi et al, 2002;Matsuyama et al, 2003), chondrosarcomas (Masi et al, 2002) and osteochondromas (Deirmengian et al, 2008) and in tumors which preferentially Promotes bone formation and fracture healing and increases bone mass of grafted bone in mice Hirotani et al (2002), Sakai et al (2000b), Sakai and Eto (2001) Abnormal craniofacial development in knock out mice deficient in either activin A or type II receptor Matzuk et al (1995a), Matzuk et al (1995b) a The effects of activin on osteoblasts are controversial (see text for details).…”
Section: Activin In Metastatic Bone Diseasesupporting
confidence: 53%
“…These studies show that this molecule (i) is one of the most abundant members of the TGF-b superfamily of growth factor present in the bone (Ogawa et al, 1992;Funaba et al, 1996;Eiken et al, 2007;Nicks et al, 2009), (ii) is actively released from bone matrix during bone resorption (Sakai et al, 2000a;Sakai and Eto, 2001;Gaddy-Kurten et al, 2002;Eiken et al, 2007), (iii) is highly expressed in osteoclasts (Funaba et al, 1996;Hosoi et al, 1996;Sakai et al, 2000a;Nicks et al, 2009), in osteoblasts (Hashimoto et al, 1992;Gaddy-Kurten et al, 2002;Eiken et al, 2007;Nicks et al, 2009) and in bone marrow cells (Gaddy-Kurten et al, 2002;Nicks et al, 2009), (iv) promotes bone formation and fracture healing and increases the bone mass of grafted bone in mice (Sakai et al, 2000b;Sakai and Eto, 2001;Hirotani et al, 2002). Moreover, in vivo studies with knock out mice deficient in either Act A or Act A type II receptor report that these animals showed an abnormal craniofacial development (Matzuk et al, 1995a,b).…”
Section: Activin In Bone Remodelingmentioning
confidence: 98%
“…Activin A, a homodimer of the hA subunit, is abundant in bone matrix (Ogawa et al, 1992) and plays a role in bone formation (Hirotani et al, 2002). We observed expression of the hCHL2 protein in epithelial cells of several human tissues, including uterine epithelium, and in osteoblasts.…”
Section: Discussionmentioning
confidence: 74%
“…Like BMPs, activin A is abundant in bone matrix (Ogawa et al, 1992) and plays a role in bone formation (Hirotani et al, 2002). Furthermore, activin A has been shown to repress muscle differentiation (Link and Nishi, 1997) and support osteoblast formation (Gaddy-Kurten et al, 2002) in cell cultures.…”
Section: Differential Expression Of Chl2 Alternatively Spliced Varianmentioning
confidence: 98%
“…It has been reported that the topical application of activin A increased the bone mass of isografted bone by increasing both bone formation and resorption in mice [1].…”
Section: Introductionmentioning
confidence: 99%